Sea change - Parker, Robert B., 1932-; Sowers, Scott (New York, NY : Random House Audio, 2006)
Jesse Stone investigates the murder of a woman, who is found in a cove near Paradise, Massachusetts. This leads to a world of wealth and depravity centered on a couple of yacht owners from Florida and their crowd.
Random House Audio: RHCD 902.
Title from disc.
Read by Scott Sowers.
"A Jesse Stone novel"--Package.
Unabridged.
Compact disc.
Keywords: Stone, Jesse (Fictitious character) -- Fiction; Police -- Massachusetts -- Fiction; Police chiefs -- Fiction; Audiobooks; Massachusetts -- Fiction